The relationship between negative life events and quality of life in adolescents: Mediated by resilience and social support - Tang, Yinshuang; Ma, Yingjie; Zhang, Jinglin; Wang, Hong (Frontiers in Public Health, 2022)
Background: Quality of life has become an important indicator for assessing the health care of adolescents. This study aimed to explore the relationship between negative life events and quality of life in adolescents and the potential mediating roles of resilience and social support. Methods: A stratified cluster sampling technique was used to select 3860 adolescents as study participants. The Adolescent Self-Rating Life Events Check List, the Resilience Scale for Chinese Adolescents, the Social Support Rating Scale, and the Adolescent Quality of Life Scale were used by participants to rate their negative life events, resilience, social support, quality of life, respectively. The correlations between study variables were analyzed by the Pearson correlation analyses. The AMOS 26.0 software was used to explore the mediating roles of resilience and social support in negative life events and quality of life. Results: There was a negative correlation between negative life events and quality of life (β=-0.745, P < 0.05); resilience and social support played an important mediating role in the relationship between negative life events and quality of life (βResilience = -0.287, P < 0.05; βSocial support = -0.157, P < 0.05). The emotional adjustment dimension of resilience (β = -0.285, P < 0.05) and the subjective support dimension of social support (β = -0.124, P < 0.05) played the largest mediating roles, respectively. Conclusion: Negative life events were negatively correlated with adolescents’ quality of life. Strengthening resilience and social support is expected to weaken and reduce the adverse effects of negative life events on adolescents and further maintain and improve their quality of life.